Development of a Psychotherapeutic Model for Psilocybin-Assisted Treatment of Alcoholism. (July 2017) - Bogenschutz, Michael P.; Forcehimes, Alyssa A.
Research activity on the potential clinical value of classic hallucinogens and other psychedelics has increased markedly in the past two decades, and promises to continue to expand. Experimental study of hallucinogen-assisted treatment, and any future clinical use, requires the development of psychotherapeutic models that are appropriate to the disorder being treated and effectively integrated with the pharmacologic component of the treatment. To provide a framework for thinking about possible treatment models, we provide an overview of the history of psychedelic-assisted treatment, review what is known about the therapeutic mechanisms of these treatments, and consider the various purposes of psychotherapy in the context of both research and clinical use of psychedelic-assisted treatment. We then provide a description of a therapy model we have developed and are currently using in a trial of psilocybin-assisted treatment for alcoholism. Finally, we discuss advantages and disadvantages of a range of alternative models, emphasizing the need for research to determine the most effective treatment models for any indications for which efficacy becomes established.